Adolescente em conflito com a lei e a lei em conflito com o adolescente : processo de criminalização da adolescência pobre - Miranda, Geane Uliana (2016)
This research problematize the process of criminalization of poor adolescence. It carried out a historical contextualization of children and adolescents in Brazil. It covers the guiding principles of socio-educational as well as their legal frameworks. It considers appropriate statistical from the capixaba and national scenaries, with regard to criminalization, via analysis of neo-liberal penal policy. This works for the penalty and the poverty imprisonment, compared to adolescents in conflict with the law, it has set up na outcry for reducing the age of criminal liability. It is important to bear in mind that childhood criminalization process and poor adolescence did not emerge today, it is a social, historical, ethnic, racial and cultural construction. The field of research was carried out in a Primary Municipal School of Youth Education and Adult named Professor Admardo Serafim de Oliveira (EMEF EJA ASO), which is attended by many adolescents in compliance with socio-educational measures. As a methodological perspective, it uses the work of anthropologists Jeanne Fravet-Saada and Márcio Goldman. It is thought in the social facilities, such as the referred teaching unit, designed to serve the impoverished sections of the population need, all the time, to rethink and strategize to not perform the minimum State logic in social and economic spheres, producing "poor policy for poor". It is believed the perspective of access and guarantee fundamental rights and not merely compensatory policies that end up reinforcing the scapegoating of poverty. In this work, bet in a more equal society, where everyone has access to education, health, housing and income. Fight is against reductiong of criminal liability age and all other forms of criminalization, punishment and poor adolescent imprisonment.